2013
DOI: 10.3741/jkwra.2013.46.12.1235
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Climate Change Impact on Storage Behavior of Chungju and the Regulation Dams Using SWAT Model

Abstract: This study is to evaluate the climate change impact on future storage behavior of Chungju dam(2,750*10 6 m 3 ) and the regulation dam(30*10 6 m 3 ) using SWAT(Soil Water Assessment Tool) model. Using 9 years data(2002~2010), the SWAT was calibrated and validated for streamflow at three locations with 0.73 average Nash-Sutcliffe model Efficiency(NSE) and for two reservoir water levels with 0.86 NSE respectively. For future evaluation, the HadCM3 of GCMs (General Circulation Models) data by scenarios of SRES (Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…As highlighted by Velázquez et al (2013), the results of this study also show that the selection of the GCM strongly affects the impacts of climate change on runoff. This study covers a wide range of plausible climate change(12 GCMs) and therefore our results differ significantly from those of previous studies in which less GCMs, greenhouse gas concentration projectile and hydrological models are considered (Jeong et al, 2013;Kim et al, 2013b;Sohn et al, 2014).…”
Section: Projected Runoffcontrasting
confidence: 97%
See 1 more Smart Citation
“…As highlighted by Velázquez et al (2013), the results of this study also show that the selection of the GCM strongly affects the impacts of climate change on runoff. This study covers a wide range of plausible climate change(12 GCMs) and therefore our results differ significantly from those of previous studies in which less GCMs, greenhouse gas concentration projectile and hydrological models are considered (Jeong et al, 2013;Kim et al, 2013b;Sohn et al, 2014).…”
Section: Projected Runoffcontrasting
confidence: 97%
“…The study showed significant uncertainty in runoff even under the same climate change simulations due to the different hydrological and ET models. Jeong et al (2013) used one GCM and two Special Report on Emissions Scenarios (SRES) scenarios and predicted modest increases in runoff of 2.2% to 4.8% in the Chungju Basin with changes in potential evapotranspiration(ET) and soil moisture of +7.6 to +15.3% and -2.1% to -1.8%, respectively, for the 2080s. In another study, Sohn et al (2014) used 3 GCMs and one SRES scenario and reported changes in runoff from -35% to +40% by the 2080s in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…The Coupled Model Inter-comparison Project 5 (CMIP5) climate models have been used in South Korea because they consider Asian-Australian monsoon climate factor [10]. Many studies have studied the climate change impact on future dam inflow from watershed [11][12][13][14][15]. Studies of dam water supply satisfying water demands under future dam inflow and release conditions are necessary.…”
Section: Introductionmentioning
confidence: 99%